Analisis Pelayanan Terhadap Minat dan Kepuasan Konsumen. Studi pada Makanan Jalanan di Area Sudirman, Bandung, Indonesia - Fadhilah, Muhammad Faishal; Panggabean, Airlangga Dwitama Putra (Asosiasi Ahli Administrasi Indonesia, 2022)
This study aims to analyze the effect of street food services on Sudirman Street, Bandung City on consumer interest and satisfaction during the Covid-19 pandemic. The research method used is descriptive quantitative using primary data obtained through questionnaires using the google form platform which is distributed to the general public through online media to 123 respondents who have had culinary tours at Sudirman Street Food, Bandung City. The collected data were analyzed using descriptive analysis, simple linear regression and correlation analysis. The results of this study indicate that the services provided by traders at Sudirman Street Food affect buying interest by 19.9% ​​and customer satisfaction by 46.2%. The influence given by the service on buying interest and customer satisfaction is a positive influence. Thus, the higher the service quality, the higher the buying interest and customer satisfaction.